Probabilistic Planning for Predictive Condition Monitoring and Adaptation Within the Self-Optimizing Energy Management of an Autonomous Railway Vehicle - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph (Journal of Robotics and Mechatronics)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for selfoptimizing mechatronic systems and shows how probabilistic planning can be used to improve the availability and reliability of systems in the operating phase. The general idea to improve the availability of autonomous systems by applying probabilistic planning methods to avoid energy shortages is exemplified on the example of an innovative railway vehicle.
Keywords: self-optimizing systems; dependability; probabilistic planning; energy management

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Weyl asymptotics: From closed to open systems - Potzuweit, A.; Weich, Tobias; Barkhofen, Sonja; Kuhl, U.; Stöckmann, H.-J.; Zworski, M. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Doping the nematic liquid crystal 5CB with milled BaTiO3nanoparticles - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Kitzerow, Heinz-Siegfried (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Customer Interaction 2.0: Adopting Social Media as Customer Service Channel - Geierhos, Michaela (Journal of Advances in Information Technology)
Since customers first share their problems with a social networking community before directly addressing a company, social networking sites such as Facebook, Twitter, MySpace or Foursquare will be the interface between customer and company. For this reason, it is assumed that social networks will evolve into a common communication channel – not only between individuals but also between customers and companies. However, social networking has not yet been integrated into customer interaction management (CIM) tools. In general, a CIM application is used by the agents in a contact centre while communicating with the customers. Such systems handle communication across multiple different channels, such as e-mail, telephone, Instant Messaging, letter etc. What we do now is to integrate social networking into CIM applications by adding another communication channel. This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer service management and the company’s response will be delivered through the customer’s preferred social networking site.
Keywords: Social Media Business Integration; Multichannel Customer Interaction Management; Contact Centre Application Support

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Versteigerungserlöse aus CO2-Zertifikaten im Spannungsfeld zwischen Bund und Ländern - Löschel, Andreas; Reif, Christiane; Kesternich, Martin; Koesler, Simon; Osberghaus, Daniel; Korioth, Stefan
Keywords: Business; Management and Accounting (miscellaneous)

A UML Frontend for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao; Müller, Wolfgang (Proceedings of DATE'09)
IP-XACT is a well accepted standard for the exchange of IP components at Electronic System and Register Transfer Level. Still, the creation and manipulation of these descriptions at the XML level can be time-consuming and error-prone. In this paper, we show that the UML can be consistently applied as an efficient and comprehensible frontend for IP-XACT-based IP description and integration. For this, we present an IP-XACT UML profile that enables UML-based descriptions covering the same information as a corresponding IP-XACT description. This enables the automated generation of IP-XACT component and design descriptions from respective UML models. In particular, it also allows the integration of existing IPs with UML. To illustrate our approach, we present an application example based on the IBM PowerPC Evaluation Kit.
Keywords: Unified modeling language; XML; Power system modeling; Application software; Master-slave; Power system management; Acceleration; Scattering; Software engineering; Software standards

Practical Security of Large-scale Elections: An Exploratory Case Study of Internet Voting in Estonia - Schryen, Guido (7th Workshop on e-Business (WEB 2008, AIS Special Interest Group on E-Business))
The Estonian parliamentary election in 2007 is regarded as a success story of large-scale Internet elections. I use this election in a single case study on practical security to show that low quality of security and its management does not necessarily prevent large-scale Internet elections from being conducted. I also provide research propositions with regard to future challenges for large-scale Internet elections.
Keywords: Internet voting; large-scale election; Estonian parliamen- tary election; security; security management

Preparing for the ‘real’ market: national patterns of institutional learning and company behaviour in the European Emissions Trading Scheme (EU ETS) - Engels, Anita; Knoll, Lisa; Huth, Martin (European Environment)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

A Novel Similarity Measure for Positioning Cellular Phones by a Comparison With a Database of Signal Power Levels - Haeb-Umbach, Reinhold; Peschke, Sven (IEEE Transactions on Vehicular Technology)
In this paper, we propose a novel similarity measure to be used for localizing mobile terminals by comparing measured signal power levels with a database of predictions. The proposed measure provides the possibility to incorporate inherent information about signal power level measurements requested by the serving base station but not reported by the mobile terminal. Increased positioning accuracy was observed both in simulations and with real field data
Keywords: cellular phone positioning; cellular radio; measured signal power levels; mobile handsets; mobility management (mobile radio)

Sozialraum - Kessl, Fabian; Landhäußer, Sandra; Ziegler, Holger (Aktivierende Sozialpädagogik. Ein kritisches Glossar)
"Aktivierung" ist zum zentralen Leitbild der Transformation der westlichen Wohlfahrtsstaaten geworden - wenngleich sich abzeichnet, dass die Bilanzen der Politiken der "Aktivierung" eher vernichtend ausfallen. Aus sozialpädagogischer Perspektive enthält der aktuelle - vorrangig ökonomisch orientierte - sozialpolitische Aktivierungsdiskurs vielfältige Optionen, in denen genuin pädagogische Interventionsformen nur undeutlich definiert werden. Das Glossar greift derzeit zentrale Begriffe auf und positioniert und hinterfragt wichtige Referenzen sozialpädagogischer Aktivierung in ihren Kernaussagen. In der Aufarbeitung der sozialpädagogischen Qualität der einzelnen Begriffe wird offensichtlich, dass sie in der Verwendung im politischen Diskurs nicht deckungsgleich sind.
Keywords: Beratung Bildung Bürgergesellschaft Case Management Dienstleistung Erlebnisorientierung Lebenswelt Lebensweltorientierung Qualitätsmangement Sozialpädagogik Sozialraum Zivilgesellschaft

Secure Profile Management in Smart Home Networks - Ziegler, Max; Müller, Wolfgang; Schäfer, Robbie; Loeser, Chris (Proceedings of the 1st International Workshop on Secure and Ubiquitous Networks (SUN-2005))
Currently, middleware for smart home networks with embedded and mobile devices are in the focus of several investigations. In this paper, we propose a middleware for secure management of device and user profiles by integrating a profile database with a generic authentication scheme for an X.509 enabled ticket management in the context of the OSGi framework. After the introduction of the individual system components and their interaction, we also discuss potential system attacks.
Keywords: Intelligent networks; Smart homes; Middleware; Project management; Data security; Ubiquitous computing; Context-aware services; Computer architecture; Home automation; Environmental management

Profile Management technology for Smart Customization in Private Home Applications - Groppe, Jinghua; Müller, Wolfgang (Proceedings of the 1st International Workshop on Secure and Ubiquitous Networks (SUN-2005))
Smart homes provide their users with maximum comfort and convenience. In this paper, we present a profile management framework for situation-dependent customization in smart home environments, which meet the user preferences with given device capabilities. We apply profile processing and evolution methods to customize profiles on the fly and to automatically evolve user preferences. Furthermore, we give a comprehensive study on profile management technology.
Keywords: Technology management; Smart homes; Environmental management; Resource description framework; Data models; Navigation; Mobile computing; Embedded computing; Ubiquitous computing; Mobile communication

An ASM Definition of the Dynamic OCL 2.0 Semantics - Flake, Stephan; Müller, Wolfgang (Proceedings of the UML 2004)
The recently adopted OCL 2.0 specification comes with a formal semantics that is based on set theory with a notion of an object model and system states. System states keep the runtime information relevant for the evaluation of OCL expressions. However, not all new language concepts of OCL 2.0 are already addressed in that formal semantics. We show how to overcome this by introducing new components to the object model and system states defining a dynamic semantics of OCL. In order to give precise rules that determine when the current system state has to be updated according to a change in the referred UML model, we make use of adequate mathematical means, namely Abstract State Machines (ASMs). Though our ASM specification also gives a clear definition for the evaluation of OCL constraints, it leaves sufficient flexibility for application specific implementations that have to determine when constraints are to be checked.
Keywords: System State Formal Semantic Object Management Group Denotational Semantic Dynamic Semantic

Scheduling in HPC Resource Management Systems: Queuing vs. Planning - Hovestadt, Matthias; Kao, Odej; Keller, Axel; Streit, Achim (Proc. Workshop on Job Scheduling Strategies for Parallel Processing (JSSPP))
Nearly all existing HPC systems are operated by resource management systems based on the queuing approach. With the increasing acceptance of grid middleware like Globus, new requirements for the underlying local resource management systems arise. Features like advanced reservation or quality of service are needed to implement high level functions like co-allocation. However it is difficult to realize these features with a resource management system based on the queuing concept since it considers only the present resource usage. In this paper we present an approach which closes this gap. By assigning start times to each resource request, a complete schedule is planned. Advanced reservations are now easily possible. Based on this planning approach functions like diffuse requests, automatic duration extension, or service level agreements are described. We think they are useful to increase the usability, acceptance and performance of HPC machines. In the second part of this paper we present a planning based resource management system which already covers some of the mentioned features.
Keywords: High Performance Computing; Service Level Agreement; Grid Resource; Resource Management System; Advance Reservation

A Generic System for Interactive Real--Time Animation - Dücker, M.; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings International Conference and Workshop on Engineering of Computer-Based Systems)
The authors present a new approach to an interactive design and analysis environment for visual languages. The main components, i.e., editor animator and interpreter are introduced. Their interactions are being investigated emphasizing the interpreter-animator interaction and defining an interface supporting different levels of automation. The interpreter performs the executions on a logical level and triggers the animator. The interactive animation provides a very high degree of liveness since it is based on the tight integration of the animator and editor. The proposed architecture permits the distributed implementation of a system for real-time animation. Their concepts are validated by the implementation of a debugging environment for the complete visual programming language Pictorial Janus.
Keywords: Real time systems; Animation; Debugging; Automation; Computer languages; Timing; Environmental management; Programming environments; Visualization; Multimedia systems

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization